The Effect of Progressive Tax Implementation, Tax Sanctions and Tax Knowledge on the Level of Motor Vehicle Taxpayer Compliance in Palembang City (Case Study on WPOP Joint Office Samsat City of Palembang I) - Bela Barokah; Lukita Tripermata; Andini Utari Putri (International Journal of Community Service & Engagement, 2023)
This study aims to analyze the effect of applying progressive taxes, tax sanctions, and tax knowledge on the level of compliance of motor vehicle taxpayers in the city of Palembang (a survey of taxpayers at the Joint Samsat Office of Palembang I). The method used in this study is a descriptive method with a quantitative approach. The sources of data used in this study are primary data sources. The data collection technique used is distributing 100 questionnaires to taxpayers who register for progressive tax at the Joint Samsat Office of Palembang City I. The sampling technique in this study is non-probability sampling with incidental sampling. The data analysis method in testing the hypothesis used in this study is multiple regression analysis. The results of hypothesis testing prove that there is an effect of applying progressive taxes, tax sanctions, and tax knowledge on the level of compliance of motorized vehicle taxpayers at the Palembang City Joint Office I.